Spontaneous regression of natural killer cell lymphoma. Issue 7 (26th June 2009) - Isobe, Y; Aritaka, N; Sasaki, M; Oshimi, K; Sugimoto, K
Abstract : Spontaneous tumour regression is extremely rare in aggressive lymphoma. A case of natural killer (NK) cell lymphoma with cutaneous manifestation showed an indolent clinical course, and the relapsed nodular lesion disappeared spontaneously without any treatment. Although only small number of T cells were present in the primary skin lesion, there was massive CD8-positive cytotoxic T cell infiltration in the relapsed lesion. This is believed to be the first report of an abscopal effect on NK cell lymphoma. Infiltration of cytotoxic T cells strongly suggests immunological attack against the lymphoma cells.